2023
DOI: 10.1097/j.pain.0000000000002922
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk shared across 24 chronic pain conditions: identification and characterization with genomic structural equation modeling

Abstract: Chronic pain conditions frequently co-occur, suggesting common risks and paths to prevention and treatment. Previous studies have reported genetic correlations among specific groups of pain conditions and reported genetic risk for within-individual multisite pain counts (≤7). Here, we identified genetic risk for multiple distinct pain disorders across individuals using 24 chronic pain conditions and genomic structural equation modeling (Genomic SEM). First, we ran individual genome-wide association studies (GW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 116 publications
(177 reference statements)
0
2
0
Order By: Relevance
“…A longitudinal, psychometric analysis has supported the validity of a common component underlying pain across body sites (Battaglia et al, 2022). Consistent with this psychometric evidence for a general pain factor, twin and genome-wide association studies have identified a common genetic factor that contributes to many chronic pain conditions (Vehof et al, 2014;Zorina-Lichtenwalter et al, 2023). Of the people who reported pain in our sample, 97.2% reported pain lasting more than 3 months, characterizing the measure as chronic.…”
Section: Brief Pain History Questionnairesupporting
confidence: 78%
“…A longitudinal, psychometric analysis has supported the validity of a common component underlying pain across body sites (Battaglia et al, 2022). Consistent with this psychometric evidence for a general pain factor, twin and genome-wide association studies have identified a common genetic factor that contributes to many chronic pain conditions (Vehof et al, 2014;Zorina-Lichtenwalter et al, 2023). Of the people who reported pain in our sample, 97.2% reported pain lasting more than 3 months, characterizing the measure as chronic.…”
Section: Brief Pain History Questionnairesupporting
confidence: 78%
“…Variants associated with drinks per week, schizophrenia, smoking initiation, and bipolar disorder were mapped to synaptosome associated protein 91 (SNAP91). The chromosome 17 Pehlq1 interval maps to regions on human chromosomes 5 (109.5-110.7Mb) and 18 (2.57-8.83; 9.10-9.96Mb), and it features variants associated with opioid analgesic sensitivity (DLGAP1)[41], schizophrenia (MAN2A1)[42], chronic pain (TMEM200C)[43], and post-traumatic stress disorder symptomatology (DLGAP1)[44].…”
Section: Resultsmentioning
confidence: 99%
“…Our study demonstrates an interplay of genetic determinants in the manifestation of pain, corroborating previous research. Specifically, a prior network analysis has identified a substantial cluster of conditions and pinpointed arthropathic, back, and neck pain as potential hubs for cross-condition chronic pain (Zorina-Lichtenwalter et al 2023).…”
Section: Discussionmentioning
confidence: 99%